Abnormal Audit Fee And Audit Quality: A Moderating Effect of Firm Characteristics - Alexander Olawumi Dabor; Uyagu Benjamine (Faculty of Economics, Universitas Sriwijaya, 2017)
The objective of the study is to examine moderating effects of client characteristics on the relationship between abnormal audit fee and audit quality. Specifically the study examines the moderating of client risk, client complexity and client profitability on the relationship between abnormal audit fee and audit quality. A random sample of fifty-two quoted companies was used for the study and data covering fifteen years (2001-2015) were extracted from the reports of selected firms. The study employed least square regression technique analyse data collected from field. The study found that there is no significant relationship between abnormal audit fee and audit quality. The result also showed client complexity and client profitability have negative moderating influence on the relationship between abnormal audit fee and audit quality. The study further revealed that client risk has no significant moderating influence on the relationship between abnormal audit fee and audit quality. The study recommended that statutory bodies should further securitize the audited financial reports of firms that declare huge profit.